Verbal Communication On Youtube Live Streaming Content Of Mobile Legends Channel Top Global Miya About Changes In Teenage Behavior - Suslia ningrum; Rizki Septian Firmansyah; Lulu Luqyana Najmi; Khaerudin Imawan (PT Publikasiku Academic Solution, 2024)
The use of YouTube has various impacts on its users, especially on teenagers who like to watch live-streaming content of Mobile Legends games on Miya's Top Global channel. This study aims to analyze verbal communication in the live streaming content and identify changes in adolescent behavior after watching. The research method used is qualitative, using data triangulation techniques through interviews, observations, and documentation. The results of the study show that the Mobile Legends live streaming content on the Top Global Miya channel has a significant impact on adolescents' verbal communication, such as the use of coarse language, increased vocabulary related to the game, and changes in intonation and speaking speed. The discussion highlighted that although there is an improvement in more precise and concise communication skills, there are also negative impacts, such as the use of offensive language and verbal violence. In conclusion, this live-streaming content contributes to the formation of adolescent communication patterns that are not in accordance with social norms, and parental guidance is needed to overcome these negative impacts.